Emiliano Ruiz Díaz y María Redondo (Coord.). Devociones Populares Argentinas. Buenos Aires: Biblioteca Nacional Mariano Moreno, 2023, 104 pp. - Alarcón, Santiago (Badebec, 2024)
Reseña de Emiliano Ruiz Díaz y María Redondo (Coord.). Devociones Populares Argentinas. Buenos Aires: Biblioteca Nacional Mariano Moreno, 2023, 104 pp.